Prevalence of diabetic retinopathy in Brazil: a systematic review with meta-analysis - Thiago Alves Chagas; Mateus Augusto dos Reis; Gabriel Leivas; Lucas Porto Santos; Agnes Nogueira Gossenheimer; Gustavo Barreto Melo; Fernando Korn Malerbi; Beatriz D. Schaan (Diabetology & Metabolic Syndrome, 2023)
Abstract Aims To evaluate the prevalence of diabetic retinopathy (DR) in Brazilian adults with diabetes mellitus via a systematic review with meta-analysis. Methods A systematic review using PubMed, EMBASE, and Lilacs was conducted, searching for studies published up to February 2022. Random effect meta-analysis was performed to estimate the DR prevalence. Results We included 72 studies (n = 29,527 individuals). Among individuals with diabetes in Brazil, DR prevalence was 36.28% (95% CI 32.66–39.97, I2 98%). Diabetic retinopathy prevalence was highest in patients with longer duration of diabetes and in patients from Southern Brazil. Conclusion This review shows a similar prevalence of DR as compared to other low- and middle-income countries. However, the high heterogeneity observed—expected in systematic reviews of prevalence—raises concerns about the interpretation of these results, suggesting the need for multicenter studies with representative samples and standardized methodology.